1990
DOI: 10.1021/jm00171a007
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic and computer-assisted analyses of the pharmacophore for the benzodiazepine receptor inverse agonist site

Abstract: The structural requirements for ligand binding to the benzodiazepine receptor (BzR) inverse agonist site were probed through the synthesis and in vitro evaluation of 3-substituted beta-carbolines 6, 7, 11, 12, gamma-carboline 13, and diindoles 18-21, 23-25, 27, 28, and 34. On the basis of the apparent binding affinities of these and other analogues, a hydrogen bond acceptor site (A2) on the receptor is proposed to interact with the N(9) hydrogen atom of the beta-carbolines or the N(7) hydrogen nuclei of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 4 publications
6
96
0
Order By: Relevance
“…13,14 Initially, it was believed that an ester moiety at the 3-position was required for a compound to exhibit high-affinity binding at Bz binding sites. [34][35][36][37] However, the high affinity of the partial inverse agonist 3-ethoxy--carboline 54 (Table 3) demonstrated this was not the case.…”
Section: Resultsmentioning
confidence: 99%
“…13,14 Initially, it was believed that an ester moiety at the 3-position was required for a compound to exhibit high-affinity binding at Bz binding sites. [34][35][36][37] However, the high affinity of the partial inverse agonist 3-ethoxy--carboline 54 (Table 3) demonstrated this was not the case.…”
Section: Resultsmentioning
confidence: 99%
“…Series A: This series contains 17 b-carbolines with their observed affinities (Allen et al, 1990;Good et al, 1993;Sharma et al, 1992;So et al, 1997) as reported in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the Rl group of 7 is aligned in the same way as all other type a structures. It may be, however, that Rl groups containing other oxygens need to be realigned to a position closer to a postulated pharmacophore hydrogen bond (Allen et al, 1990). One way to alter alignments, of course, would be to apply similarity optimisation to the system, since at the moment only a simple least-squares fit of the central skeletons has been undertaken.…”
Section: Similarity Matrices and Multivariate Statistical Techniquesmentioning
confidence: 98%
“…Allen et al (1990) were the first to study the benzodiazepine system using 3D QSAR techniques, employing CoMF A in order to characterize a pharmacophore for the site. This ligand set provides a good example of a system where 3D QSAR has significant advantages over more traditional methods.…”
Section: Similarity Matrices and Multivariate Statistical Techniquesmentioning
confidence: 99%